Futures of the Study of Culture : Interdisciplinary Perspectives, Global Challenges. - Bachmann-Medick, Doris. (Concepts for the Study of Culture (CSC) Series, 2020)
This series addresses key contemporary concepts and methods along with substantive issues from the realm of basic research in cultural studies. Its objective is to help shape contemporary discourse about cultural studies and at the same time to enrich this discourse for work in its specific disciplines.